2016
DOI: 10.1073/pnas.1603252113
|View full text |Cite
|
Sign up to set email alerts
|

Unreplicated DNA remaining from unperturbed S phases passes through mitosis for resolution in daughter cells

Abstract: To prevent rereplication of genomic segments, the eukaryotic cell cycle is divided into two nonoverlapping phases. During late mitosis and G1 replication origins are "licensed" by loading MCM2-7 double hexamers and during S phase licensed replication origins activate to initiate bidirectional replication forks. Replication forks can stall irreversibly, and if two converging forks stall with no intervening licensed origin-a "double fork stall" (DFS)-replication cannot be completed by conventional means. We prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(160 citation statements)
references
References 35 publications
(54 reference statements)
12
144
1
1
Order By: Relevance
“…As such, large regions of repetitive DNA will not be sequenced accurately and yet are likely to contain ROs. These false negatives imply that the largest replicons measured provide an upper bound rather than a definite value, although we do not expect large numbers of missed ROs (19). The future use of more advanced techniques, for example, single-cell sequencing, will shed more light on this aspect.…”
Section: Large Replicons In Human Genomes Cause the Most Errors But Arementioning
confidence: 80%
See 2 more Smart Citations
“…As such, large regions of repetitive DNA will not be sequenced accurately and yet are likely to contain ROs. These false negatives imply that the largest replicons measured provide an upper bound rather than a definite value, although we do not expect large numbers of missed ROs (19). The future use of more advanced techniques, for example, single-cell sequencing, will shed more light on this aspect.…”
Section: Large Replicons In Human Genomes Cause the Most Errors But Arementioning
confidence: 80%
“…The probability of DFSs is very small in yeasts due to the small genome size, and optimization of the RO positions by lowering R reduces this even further. However, as discussed above, organisms with larger genomes have a significantly higher probability of DFS events, which results in the need for additional molecular mechanisms to cope with the consequences (19), and the presence of such mechanisms means there is little to be gained in uniformly ordering ROs on the genomes. Thus, our expectation is that R should be significantly larger in organisms with larger genomes compared with the values found in yeast.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, a report from Moreno et al (20) emphasizes the importance of the interorigin spacing in generation of replication gaps: These investigators identified regions of late replication by the presence of ultrafine anaphase bridges. They showed that formation of such bridges was inversely correlated with the density of licensed origins, and, furthermore, that the numbers of bridges increased when the Mcm5 helicase, which is required for origin licensing, was targeted using RNAi (20). More work will be required to make more-specific genome-wide predictions of regions expected to be susceptible to incomplete replication.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent modeling studies, cells with large genomes enter mitosis with, on average, three underreplicated sites per cell, even in unperturbed growth conditions. This problem is exacerbated by conditions that induce replication stress or by reducing the number of origins Moreno et al 2016).…”
Section: Ufbs At Common Fragile Sitesmentioning
confidence: 99%